Ketidakpuasan Kinerja Karyawan pada Kantor Kebun PTPN III Persero Sarang Giting dalam Industri Sawit dan Karet: Dampak Jaringan yang Lambat terhadap Produktivitas Karyawan - Nabila Prahaski; Nurbaiti (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
The palm oil and rubber industry plays a central role in the Indonesian economy, with large companies such as the PTPN III Persero Sarang Giting Plantation Office acting as leaders in this sector. However, technical obstacles such as slow networks have hampered employee productivity. This research investigates the impact of slow networks on employee productivity in this plantation office. Through survey, interview and data analysis methods, this research identifies the negative impact of limited fast internet access on data input, internal communication, team collaboration and employee motivation. These findings provide deep insight into how these technical obstacles affect operational efficiency and employee psychological well-being. This research also proposes remedial measures including improving network infrastructure, employee training, and psychological support to overcome employee performance dissatisfaction. By implementing these recommendations, it is hoped that this garden office can increase employee productivity and ensure smooth operations in the future.